1993
DOI: 10.1093/geront/33.3.386
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Elder Abuse and Help-seeking Patterns Among African-American, Caucasian American, and Korean-American Elderly Women

Abstract: Thirteen scenarios were used to measure and compare the perceptions of elder abuse and help-seeking behaviors of African-American, Caucasian American, and Korean-American elderly women. Significant group differences existed in their perceptions of elder abuse with regard to six scenarios, and the Korean-American women were substantially less likely to perceive a given situation as abusive than the other groups. The three groups also showed significant differences in their intended use of formal and informal so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(107 citation statements)
references
References 0 publications
8
97
1
1
Order By: Relevance
“…In Asian peoples, value systems such as family ties, filial piety, guilt and shame may minimise perceptions of abuse (Malley-Morrison, 2000). Moon and Williams (1993) found that Korean Americans were more tolerant of potentially abusive situations than Caucasians or African Americans.…”
Section: Correlates Of Recognition Of Elder Abusementioning
confidence: 96%
“…In Asian peoples, value systems such as family ties, filial piety, guilt and shame may minimise perceptions of abuse (Malley-Morrison, 2000). Moon and Williams (1993) found that Korean Americans were more tolerant of potentially abusive situations than Caucasians or African Americans.…”
Section: Correlates Of Recognition Of Elder Abusementioning
confidence: 96%
“…For example, while older Koreans who were interviewed in Korean were less likely than Caucasians to seek help regarding elder abuse (Moon & Williams, 1993), older Koreans who were interviewed in English were found to be similar to Caucasians (Pablo & Broun, 1997). In other words, Koreans who spoke English were no more or less reluctant than Caucasians to report their victimization.…”
Section: Limited Language Fluencymentioning
confidence: 99%
“…These perceptions are affected by cultural values, attitudes, and traditions that define what is acceptable (non-reported) or unacceptable (reported) behavior (Griffin, 1994). According to the Moon and Williams (1993) study of three ethnic groups, Korean American women were the least likely to perceive a series of scenarios as abuse (50%) compared to Caucasian American women (67%) and African American women (75%). Similarly, 36% of the Korean American women would have sought help; 62% of the Caucasian women; and 63% of the African American women.…”
Section: Factors Influencing Reporting Of Elder Abusementioning
confidence: 99%